2012
DOI: 10.5402/2012/860768
|View full text |Cite
|
Sign up to set email alerts
|

Contribution to the Taxonomy and Distribution of Six Shark Species (Chondrichthyes, Elasmobranchii) from the Gulf of Thailand

Abstract: A collection of nine shark specimens from six different species, obtained in 1993 from the Gulf of Thailand, was examined in this study. The sharks were determined, morphometrically and meristically analyzed, photographically documented, and compared with relevant literature. Additionally, further available material from the fish collections of the Zoological Museum Hamburg, the Senckenberg Naturmuseum Frankfurt, and the Muséum national d'Histoire naturelle, Paris, was examined by way of comparison. Contrary t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 13 publications
(22 reference statements)
0
11
0
Order By: Relevance
“…These two species dominated the landings by number (46·3 and 18·8% respectively) and also contributed greatly to the total biomass of the landings (15·7 and 11·3% respectively). White () noted that C. hasseltii is very similar morphologically to the grey bamboo shark Chiloscyllium griseum Müller & Henle 1838, which is also considered to occur in Thai waters (Weigmann, ; Ebert et al, ). Thus, it should be considered that the C. hasseltii individuals recorded in this study may have contained some individuals of C. griseum .…”
Section: Family Hemiscylliidaementioning
confidence: 99%
“…These two species dominated the landings by number (46·3 and 18·8% respectively) and also contributed greatly to the total biomass of the landings (15·7 and 11·3% respectively). White () noted that C. hasseltii is very similar morphologically to the grey bamboo shark Chiloscyllium griseum Müller & Henle 1838, which is also considered to occur in Thai waters (Weigmann, ; Ebert et al, ). Thus, it should be considered that the C. hasseltii individuals recorded in this study may have contained some individuals of C. griseum .…”
Section: Family Hemiscylliidaementioning
confidence: 99%
“…Annandale 1909 is a junior synonym of H. undulata ; westernmost confirmed record in the Indian Ocean off western Malaysia (Weigmann, 2011). Also reported off India (from the Gulf of Mannar)…”
Section: Trygon Favusmentioning
confidence: 99%
“…In the present study a new maximum total length (TL) was identified for C. dussumieri (114 cm TL); in previous studies from other parts of the world the maximum TL was reported as 101 cm by Cortés (), 75 cm by Weigmann (), and 100.7 cm by White (). For C. macloti the TL from the present samples was less than that reported in earlier studies (Assadi & Dehghani, ; Last & Stevens, ).…”
Section: Discussionmentioning
confidence: 45%
“…In the present study a new maximum total length (TL) was identified for C. dussumieri (114 cm TL); in previous studies from other parts of the world the maximum TL was reported as 101 cm by Cortés (2000), 75 cm by Weigmann (2012), and 100.7 cm by White (2012).…”
Section: Discussionmentioning
confidence: 46%